The Relationship Between Self-Criticism and Hemoglobin A1c Levels in Patients with Type 2 Diabetes Mellitus - Kristanti, Erva Elli; Sari, Dyah Ayu Kartika Wulan (Babali Nursing Research, 2025)
Background: Until now, Type 2 DM is still one of the metabolic diseases with a prevalence that continues to increase globally, including Indonesia. The problem that arises is that psychosocial factors, including distress due to diabetes, self-compassion, and self-criticism, have been identified as factors that can affect glucose regulation and quality of life of Type 2 DM patients. The Purpose of this Study is to Identify the Relationship Between Self-Criticism and Hemoglobin A1c Levels in Patients with Type 2 Diabetes Mellitus Methods: This study employed a correlational design to examine the relationship between self-criticism with the glucose index in patients with type 2 Diabetes Mellitus at the Pesantren I Primary Health Center, Kediri City. The Self-criticism was assessed using the Forms of Self-Criticizing/Attacking and Self-Reassuring Scale (FSCRS), and Hemoglobin A1c levels were examined using a Portable Analyzer.  The collected data were analyzed using the regression test (α < 0.05)Bottom of Form. Results: The study showed that the self-criticism of Type 2 DM sufferers was mostly high (66%), with the results of the Hemoglobin A1c Levels being mostly abnormal (67%). There is no relationship between Self-Criticism and Hemoglobin A1c Levels of Type 2 DM sufferers (p = 0.96). Conclusion: Self-criticism does not directly affect the hemoglobin A1c levels. The findings emphasize that Hemoglobin A1c Levels in patients with diabetes mellitus are predominantly influenced by biological factors (such as dietary adherence, physical activity, pharmacological therapy, and metabolic conditions), rather than by a single psychological factor such as self-compassion.